Growth and inclusion trajectories of Colombian functional territories (2018)
We describe the patterns of economic growth and social progress in Colombian ¿functional territories". Unlike political/administrative divisions that emerge at least partly for historical reasons unrelated to economic interactions, functional territories reflect the patterns of spatial agglomeration and economic interactions in a territory. Using a novel definition of functional territories, our analysis reveals significant fragmentation of economic interactions: close to 66% of municipalities (holding about 20% of the country's population) have no significant links to neighboring areas. A set of comparatively more (but still only partially) integrated and more populous municipalities have stronger links between them. This \rural-urban" space holds just around 31% of total population. The rest of Colombians are in \urban" or \Metropolitan" highly-populated and more integrated clusters. We describe these territories along two dimensions: economic growth or \dynamism" and progress in social indicators or \inclusion". To do so we propose a simple conceptual framework that organizes the diverse inputs that might help boost these outcomes. Larger and more urbanized agglomerations exhibit visible advantages in these inputs. Moreover, long-run institutional determinants best help differentiate territories. Consistent with this, larger and more urbanized agglomerations have better outcomes, especially when measuring economic activity. Also, more dynamic places tend to be the more inclusive ones, even though recent improvements in dynamism do not correlate with improvements in inclusion.